Attunement architectural meaning after the crisis of modern science - Pérez Gómez, Alberto 1949- (The MIT Press, 2016)
"Architecture remains in crisis, its social relevance lost between the two poles of formal innovation and technical sustainability. In Attunement, Alberto Pérez-Gómez calls for an architecture that can enhance our human values and capacities, an architecture that is connected--attuned--to its location and its inhabitants. Architecture, Pérez-Gómez tells us, operates as a communicative setting for societies; its beauty and its meaning lie in its connection to human health and self-understanding. Our physical places are of utmost importance for our well-being. Drawing on recent work in embodied cognition, Pérez-Gómez argues that the environment, including the built environment, matters not only as a material ecology but because it is nothing less than a constituent part of our consciousness. To be fully self-aware, we need an external environment replete with meanings and emotions. Pérez-Gómez views architecture through the lens of mood and atmosphere, linking these ideas to the key German concept of Stimmung--attunement--and its roots in Pythagorean harmony and Vitru-architecture--the voices of architecture and the voice of the architect; architecture as a multisensory (not pictorial) experience, with Piranesi, Ledoux, and Hejduk as examples of metaphorical modeling; and how Stimmung might be put to work today to realize the contemporary possiblities of attunement"--Back cover.